1996
DOI: 10.1007/s004649910009
|View full text |Cite
|
Sign up to set email alerts
|

ERCP in association with laparoscopic cholecystectomy

Abstract: Although there is an increasing tendency to clear the bile duct with a laparoscopic approach, ERCP and sphincterotomy has a certain role in conjunction with LC in the management of patients with a high suspicion of CBD stones, particularly in institutions where there is easy access to expert interventional endoscopic techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…If ES is performed preoperatively, a two-stage treatment is necessary since it is followed by LC (sequential treatment) and thus accumulates the risks of the two techniques, the morbidity being of the order of 7% on average in the literature [2,5,11,12,20]. Moreover, the rate of detection of CBDS during retrograde endoscopic cholangiography is relatively low, since it varies between 50% and 60% [2, 11-13, 16, 20].…”
Section: Discussionmentioning
confidence: 99%
“…If ES is performed preoperatively, a two-stage treatment is necessary since it is followed by LC (sequential treatment) and thus accumulates the risks of the two techniques, the morbidity being of the order of 7% on average in the literature [2,5,11,12,20]. Moreover, the rate of detection of CBDS during retrograde endoscopic cholangiography is relatively low, since it varies between 50% and 60% [2, 11-13, 16, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment in two stages, which combines a preoperative ES followed by LC (sequential treatment), accumulates the morbidity of the two techniques and also has a relatively low detection rate of CBDS, in the range of 50–60%, during ERC [5, 14, 16, 19, 20]. Postoperative ES performed after LC has the advantages of maintaining minimally invasive treatment and of avoiding an unnecessary ERC.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Others advocate endoscopicbased therapy as a means of decreasing immediate morbidity and mortality particularly in patients who are high-risk surgical candidates, who are in a center with skilled endoscopists, and in whom there is a high suspicion of CBDS. [12][13][14] Recently, a meta-analysis of 12 studies revealed that outcome-defined as successful duct clearance, mortality, overall morbidity, and need for additional procedures-was not significantly different between surgery-only and endoscopy-plus-surgery-treated groups. 15 In light of variations in treatment and, ultimately, the lack of a consensus about the "best" way to manage these disease processes, many hospitals do not have definitive triage and management pathways for patients admitted with uncomplicated GP and CBDS.…”
Section: Introductionmentioning
confidence: 98%